The Effect of Attendance, Work Facilities, and Work Environment on Employee Performance - Dokman Marulitua Situmorang; Albert Yansen (Department of Management - Institut Shanti Bhuana, 2022)
This study aims to determine the effect of attendance, work facilities, and work environment on employee performance at PT Indomarco Prismatama. The subjects in this study were permanent employees of the Development Department of PT Indomarco Perismatama Distribution Center Jakarta 2. The data used in this study were primary data obtained from questionnaires. The sample used in this study were 79 respondents. The sampling technique is simple random sampling (random sampling). The method used in this study is quantitative using multiple linear regression analysis, coefficient of determination test (R2), partial test (t), and simultaneous test (F) which is processed using the Statistical Package for the Social Sciences (SPSS) version 23. Results shows that absenteeism, work facilities, and work environment have a positive and significant effect on employee performance. The work environment variable on employee performance has the most dominant influence